Interleukin‐19 ameliorates experimental autoimmune encephalitis. Issue 3 (18th April 2021) - Takeuchi, Hideyuki; Horiuchi, Hiroshi; Parajuli, Bijay; Komiya, Hiroyasu; Tanaka, Fumiaki; Suzumura, Akio
Abstract : Interleukin‐19 serves as a negative feedback regulator to limit the pro‐inflammatory response of macrophages and microglia in autocrine/paracrine manners. Interleukin‐19 suppresses microglia/macrophage antigen presentation, T helper 17 cell expansion and subsequent inflammation in the central nervous system, resulting in improvement in experimental autoimmune encephalomyelitis.